Motivación como estrategia didáctica en el aprendizaje significativo en los niños del subnivel 1 de la unidad educativa Juan Celio Secaira - Garrido Morocho, Melina Fernanda (2021)
This research was carried out in the Juan Celio Secaira Educational Unit of the Montalvo cantón, during the period of May - August 2021. The problem identified is that teachers do not effectively apply motivational activities to achieve better results in the teaching process. The study is to determine the relationship between motivation as a didactic strategy and meaningful learning. The applied methodology contains a non-experimental study with a qualitative-quantitative approach, descriptive and correlational scope, the types of research are documentary and field; the methods used are inductive and deductive; a sample of 7 teachers and 20 students from sublevel 1 was used, the investigative techniques to obtain information from primary sources were the survey and interview. The main results indicate that the students' level of significant learning is not at optimal levels; Furthermore, teachers do not apply motivational activities adequately and consistently. The study concludes stating that the weaknesses in the teaching process are little empowerment of the importance of motivation in education by teachers and lack of professional instruction regarding applicable methodologies in the context of student motivation.